Mittlere Schwingungsamplituden von AlH4− und AlD4− - Baran, Enrique José (1975)
The mean amplitudes of vibration for the tetrahedral AlH4− and AlD4− ions have been calculated from known spectroscopic data. The results are briefly discussed.